A novel enemy of cancer: recent investigations into protozoan anti-tumor properties - Zheng, Zhi; Lu, Xiao; Zhou, Dong; Deng, Xu-feng; Liu, Quan-xing; Liu, Xiao-bing; Zhang, Jiao; Li, Yan-qi; Zheng, Hong; Dai, Ji-gang (Frontiers in Cellular and Infection Microbiology, 2024)
Cancer remains a significant global health issue, despite advances in screening and treatment. While existing tumor treatment protocols such as surgery, chemotherapy, radiotherapy, targeted therapy, and immunotherapy have proven effective in enhancing the prognosis for some patients, these treatments do not benefit all patients. Consequently, certain types of cancer continue to exhibit a relatively low 5-year survival rate. Therefore, the pursuit of novel tumor intervention strategies may help improve the current effectiveness of tumor treatment. Over the past few decades, numerous species of protozoa and their components have exhibited anti-tumor potential via immune and nonimmune mechanisms. This discovery introduces a new research direction for the development of new and effective cancer treatments. Through in vitro experiments and studies involving tumor-bearing mice, the anti-tumor ability of Toxoplasma gondii, Plasmodium, Trypanosoma cruzi, and other protozoa have unveiled diverse mechanisms by which protozoa combat cancer, demonstrating encouraging prospects for their application. In this review, we summarize the anti-tumor ability and anti-tumor mechanisms of various protozoa and explore the potential for their clinical development and application.